The female role in quilombola sociability in the context of arrudas: notes and articulations with popular education (Research, Society and Development, 2022)
This article is linked to an issue of relevant importance for reflective analysis in regional development: the emancipatory possibilities around societal experiences in the field that are not limited to the commodity form as centrality and foundation for the existence of the social being. It is worth investigating the political accentuation that quilombola sociability can reveal from its local specificity. Therefore, at first, it is intended to explain the more general parameters about the social experience of the Quilombo in the Cariri region in close connection with the phenomenon of culture. Then, the historically constituted corporate specificity of the Arrudas region will be addressed. This shift allows us to understand in a more systematic way the historical constitutive role of women in the local community, the specific object of this article. In this way, the theoretical-methodological position in question allows us to hypothesize that the sociability present in the community of Arrudas, with special attention to the role of women, can become a fertile ground for emancipatory experiences in popular education, due to the pedagogical contents are in dynamic and intense articulation with the substrate of social action of local subjects in their daily lives. This mediation will be based on the concept of Good Living, strictly linked to quilombola sociability because it brings in its principles relations of production, exchange and cooperation based on community solidarity, and not on individualism and the commodification of all aspects of life and relationships. human. In other words, the rescue of the concept of Good Living as an intrinsic element to quilombola sociability is understood here in theoretical-methodological terms to think about this social experience as a critical formative component that effectively enables other possibilities of development beyond the hegemonic capitalist notion.